2018
DOI: 10.1186/s12888-018-1621-2
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of physical and mental health consequences among Chinese parents who lost their only child

Abstract: BackgroundThe term “loss-of-only-child family” means that the only child in a family passed away or is disabled due to an accident or other events. The parents who cannot conceive or do not adopt another child, are known as Shidu parents in China. This study compares the physical and mental health of Shidu parents with those parents who have not experienced such loss.MethodsThe target group is comprised of parents being Shidu for more than 1 year (N = 95) and the control group is comprised of parents with a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 26 publications
(21 reference statements)
4
69
1
Order By: Relevance
“…Even after 18 years-a longer period of the child's death, Christiansen et al found there still existed PTSD symptoms in the SDPs [10]. Consistently, we found SDPs had a higher risk of the development of PTSD compared to the parents with a living child, and the rate of PTSD in the Shidu group (n = 95) was up to 32.6% in a published research of our team [11]. Regarding the previous studies, the prevalence of PTSD in older people ranged from 4 to 14% following traumatic experiences such as natural disasters, physical injuries, and threat of illness [12][13][14].…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…Even after 18 years-a longer period of the child's death, Christiansen et al found there still existed PTSD symptoms in the SDPs [10]. Consistently, we found SDPs had a higher risk of the development of PTSD compared to the parents with a living child, and the rate of PTSD in the Shidu group (n = 95) was up to 32.6% in a published research of our team [11]. Regarding the previous studies, the prevalence of PTSD in older people ranged from 4 to 14% following traumatic experiences such as natural disasters, physical injuries, and threat of illness [12][13][14].…”
Section: Introductionsupporting
confidence: 88%
“…The questionnaires for physical health outcomes were the same to the previous study [11]. Two items were all included.…”
Section: Measurementioning
confidence: 99%
See 1 more Smart Citation
“…These studies showed that losing only child has adverse effects on mental health, loneliness, happiness and general emotional well-being through investigations using a data from the China Health and Retirement Longitudinal Study (CHARLS) 2011 baseline data, which was initiated to study the elderly population of China and published in March 2012 with the measures of a 10-item Center for Epidemiological Studies Depression Scale (CES-D Scale) and other self-adopted questionnaires about variables regarding losing children, Individual demographic, socioeconomic and health status A new study in our research team is undertaken to compare SDP (a sample of 95 participant) with their counterparts (97 participants) with a living child by a series of standardized assessments of their physical health and mental health problems such as PTSD and depression 25 . In terms of mental assessments, it adopted the 20-item Center for Epidemiological Studies Depression Scale (CES-D) and PTSD Checklist-Civilian Version (PCL-C).…”
Section: Current Studies Of the Chinese Sdp On The Mental And Physicamentioning
confidence: 99%
“…If parents lose their only child in adulthood this may further impact the feeling of loss as bearing another child is not possible. Previous research has demonstrated that Chinese parents who lost their only child present with significant symptoms of anxiety, depression and PTSD as well as significant impairments in physical and social areas compared to non-bereaved counterparts (Cao, Yang, & Wang, 2018; Yin et al, 2018; Zheng, Lawson, & Anderson Head, 2017). …”
Section: Introductionmentioning
confidence: 99%